2010
DOI: 10.1002/ppul.21292
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory impedance and bronchodilator response in healthy Italian preschool children

Abstract: Summary. Objective: To define normal values for respiratory resistance (R rs ) and reactance (X rs ) and bronchodilator response (BDR) in a population of healthy Italian preschool children using a commercially available forced oscillation device. Methods: R rs and X rs were measured in kindergartens in Viterbo, Italy. Regression analysis was performed taking into account height, weight, age, gender, and reference equations calculated. The coefficient of repeatability (CR) between two tests performed 15 min apa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 22 publications
10
37
0
Order By: Relevance
“…In the current study, the bronchodilator response was expressed as the relative change compared with the baseline value, as suggested by THAMRIN et al [14]. Expression of the response as the absolute change or as the change in terms of the z-score, as recently suggested by CALOGERO et al [12], yielded similar results.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the current study, the bronchodilator response was expressed as the relative change compared with the baseline value, as suggested by THAMRIN et al [14]. Expression of the response as the absolute change or as the change in terms of the z-score, as recently suggested by CALOGERO et al [12], yielded similar results.…”
Section: Discussionsupporting
confidence: 55%
“…Several previous studies using the FOT in preschool children have demonstrated that current standing height is the main anthropometric determinant of the baseline lung function [12][13][14]23]. These previous studies were all cross-sectional studies of healthy children with a broader age and thus height range than those of the children participating in our study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the literature, several reference equations for FOT, both for preschool children and older children, have been reported [1,2,9,10]. Data are also available on BDR [1], and many studies suggest that a decrease in Rrs of 20%-40% compared with baseline should be considered as a positive response to bronchodilators.…”
Section: The Forced Oscillation Techniquementioning
confidence: 99%
“…Data are also available on BDR [1], and many studies suggest that a decrease in Rrs of 20%-40% compared with baseline should be considered as a positive response to bronchodilators. A recent study conducted on healthy Italian preschool children suggested to use a cut-off that corresponds to a change in the Z-score of -1.88 for Rrs8 and 2.48 for Xrs8 [9].…”
Section: The Forced Oscillation Techniquementioning
confidence: 99%